The Role of Certification of Indonesian Ship’s Crew - Ong Argo Victoria; Bambang Setiawan; Agus Darmawan; Purboyo Purboyo (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2020)
With the demands of seafarers' standards set by the International Maritime Organization (IMO). Global seafarers, including those from Indonesia, must follow the terms and conditions of the 2010 Manila Amendment Standards of Training, Certifitation and Watchkeeping (STCW). The competence of fishing vessel crews is one of the main factors supporting the success of fishing operations. Mastery of crew competence is proven by competency certificates obtained through education and training as well as certification tests for fishing vessel crews by the competent authority. Competency standards for fishing vessel crews must be in accordance with the size of the vessel (vessel length and gross tonage) and the area of the fishing operation. This study aims to examine the gaps that occur between the competency certificates of fishing vessel crews and the prevailing laws and regulations in Indonesia and the contributing factors. Research has been carried out on ships with a size of more than 30 GT at the Nusantara Pelabuhan Ratu Fishery Port and Nizam Zachman Muara Baru Fishery Port, Jakarta. Primary data is obtained from documentary evidence of the crew (BST, Seaman's Book, Ankapin, Atkapin, SKK) who were on the ship. Secondary data were obtained from the ship's crew license, SPB, size of the ship (length and GT), the area of fishing operations and the prevailing laws and regulations on fishing vessel manning in Indonesia. Data processing was carried out using descriptive analysis methods with a qualitative approach. The results showed that the majority of Indonesian fishing vessel crews do not have competency certificates according to applicable regulations. This is due to the dispensation of SPB issuance and the limited time for conducting the certification test. The authorities must firmly determine the deadline for the dispensation of SPB issuance and increase the time and place for certification testing that is easily accessible to the crew.